Papanicolaou sampling during menstruation: evaluation in four Lima hospitals - López, Lucy (2011)
Objectives: To analyze adequate Papanicolaou obtention feasibility during menstruation by thoroughly and softly cleaning the uterine cervix from blood before securing the sample. Design: Correlation prospective study of repeated measurements. Participants: Women in reproductive age. Methods: Three hundred and eighty nine women attending four Lima South region hospitals participated in the study; analysis was done in 208 of them after obtaining a pair of Papanicolaou smears from each woman corresponding to their menstrual and non menstrual periods. The smear taken during menstruation was collected after careful and soft cleaning of the uterine cervix and waiting for absence of menstrual pulse through the cervical os. Two pathologists studied the smears separately. Main outcome measures: Adequacy of Papanicolaou samples obtained during menstruation. Results: Smear samples from menstrual and non menstrual periods were adequate for cytodiagnosis and showed no significant statistical difference (p< 0.005) in two hospitals where health providers had been trained and motivated. In the other two hospitals, where most of the samples were collected by health providers without training, 75% of the smears were obscured by hemorrhagic tissue, inadequate for Papanicolaou cytodiagnosis. There was significant statistical difference between samples obtained with menstruation and without menstruation (p < 0.005). Conclusions: It is possible to obtain an adequate sample for Papanicolaou study during menstruation provided health personnel knows the technique to obtain a smear without blood and is motivated to do so. This procedure can increase access to preventive measures for uterine cervix cancer control.